Relationship between oxidative stress and COVID-19 severity: A systematic review and meta-analysis - Alam, Mohammad Shah; Hasan, Mohammad Nazmol; Sharif, Md Arman; Islam, Md Shahidul; Rahman, Md Mizanur; Shahrier, Rafee; Bostami, A B M Rubayet; Saha, Mousumi; Islam, Md Sodrul; Nazir, K H M Nazmul Hussain (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: COVID-19 is a complex disease in which the interaction of the SARS-CoV-2 virus with target cells, activation of the immune system, and release of inflammatory cytokines are closely intertwined. Oxidative stress is associated with all of these events, which significantly contribute to the pathogenesis of COVID-19. This study aimed to analyze the relationship quantitatively between oxidative stress and the disease severity in hospitalized patients. Methodology: Articles measuring pro-oxidant and antioxidant markers in patients with COVID19 were retrieved through the search engines ScienceDirect, PubMed, and Google Scholar. Two authors independently extracted data using the data extraction tool, and a third arbitrator was consulted if consensus was not reached. Data were subjected to meta-analysis using the “meta” package of R programming for forests and the trim and fill method under a random-effects model based on standardized mean differences (SMDs). We tested for heterogeneity in effect size using the I² statistic and Egger’s test to assess bias. Results: Of the 3,103 articles screened, 17 met the inclusion criteria. When comparing control vs. mild cases, control versus severe cases, and mild versus severe cases, hydrogen peroxide (H₂O₂) levels were significantly increased [(SMD, 2.46; CI: –0.81 to 5.73; p = 0.05), (SMD, 3.22; CI: –0.70 to 7.14; p = 0.05), and (SMD, 0.49; CI: –0.23 to 1.20; p < 0.05), respectively]. Similarly, total oxidative stress (TOS) levels were significantly increased when comparing control versus mild cases (SMD, 4.01; CI: 0.85 to 7.18; p = 0.01), control versus severe cases (SMD, 6.51; CI: –0.59 to 13.62; p = 0.07), and mild versus severe cases (SMD 3.07; CI: 01.21 to 7.36; p = 0.05). However, superoxide dismutase (SOD) levels were decreased when comparing control versus mild cases (SMD, –0.60; CI: –1.31 to 0.12; p = 0.05), control versus severe cases (SMD, –1.68; CI: –4.00 to 0.64; p = 0.05), and mild versus severe cases (SMD, –0.73; CI: –1.81 to 0.36; p = 0.06). Similarly, catalase and glutathione levels were decreased when comparing control versus mild cases, control versus severe cases, and mild versus severe cases. Moreover, thiol levels were significantly decreased when comparing control versus mild cases (SMD, –1.72; CI: –2.91 to –0.53; p = 0.005), control versus severe cases (SMD, –2.83; CI: –3.97 to –1.69; p = 0.00), and mild versus severe cases (SMD, –1.19; CI: –1.83 to –0.54; p = 0.00). Conclusion: This meta–analysis revealed significantly higher levels of pro-oxidants (H₂O₂ and TOS) and lower levels of antioxidants (SOD, CAT, GSH, and thiols) in severe cases of COVID-19 compared to controls and mild cases, indicating that oxidative stress contributes to the severity of the disease. Assessing pro-oxidant and antioxidant stress markers may help assess disease severity for effective triage of COVID-19 patients. This information will be valuable for a broader discussion on the pathogenesis of COVID-19. J. Adv. Vet. Anim. Res., 12(3): 975–987, September 2025 http://doi.org/10.5455/javar.2025.l957